The urgency of the Second Amendment to Law Number 12 of 2011 concerning the Formation of Regulations Legislation - Conie Pania Putri; Nuril Furqon (International Journal of Business, Economics, and Social Development, 2022)
In order to create a legal objective to protect and provide the people with fair treatment, the law should protect every citizen of the nation so that their rights are guaranteed in state regulations. The regulation is also used as guidelines in the further preparation of legislation. With the existence of standard procedure, each drafting of regulations such as defining, standardization, and choosing a method that binds all institutions authorized to form laws and regulations so that the regulations in question can meet the needs of the community for good laws and regulations. The 1945 Constitution of the Republic of Indonesia itself has mandated Law Number 12 of 2011 concerning the Establishment of Legislation to be a guide in forming legislation, one of the proposed changes from the Second Draft Amendment to Law Number 12 of 2011 concerning the Establishment of Legislation is to add the omnibus law method. The legislation technique with the omnibus law model was chosen to be used by law policymakers in various countries for a number of reasons. One of the main reasons is that with this technique, it will be easy for legislators to reach an agreement or approval of new legislation drafts and avoid political impasse/interest.